Seroprevalence of antibodies for pertussis and diphtheria among people leaving or entering China: a cross-sectional study - Hui Han; Zhiqiang Fang; Xiangguang Ye; Hailei Wu; Feng Zuo; Quan Shi; Jinping Mu; Baoliang Xu (Journal of Infection in Developing Countries)
Introduction: Despite high population immunity, pertussis remains one of the leading causes of vaccine-preventable deaths worldwide. The aim of this study was to determine the seroprevalence of IgG antibodies to pertussis toxin (PT) and diphtheria among the adult male population leaving or entering China.